Polymorphism of even nylons revisited through periodic quantum chemical calculations. (12th June 2015) - Galimberti, Daria; Quarti, Claudio; Milani, Alberto
Abstract: Density functional theory calculations with periodic boundary conditions have been carried out for the 3D crystal cells of α and γ polymorphs of even polyamides (ranging from nylon-4 up to nylon-12) in order to investigate the relative stability of the two forms. The infinite 1D polymer chains possessing α and γ conformations have been also simulated to shed light on the intramolecular effects taking place in these systems and to discriminate the intermolecular effects in terms of hydrogen bonding and packing of CH2 units. The results of this analysis allowed to give a detailed interpretation of the polymorphism properties observed in even nylons, predicting a larger stability for the α form in nylon-4 and nylon-6 and a stabilization of the γ phase from nylon-8 up to nylons having a larger number of CH2 unit in the chain. Graphical abstract: Highlights: The energetics ruling the polymorphism of even nylons is investigated. State-of-the-art periodic DFT calculations are applied to polymers' crystals. Competitive supramolecular effects occurring in polyamides are studied in details.